PERTUMBUHAN DAN SINTASAN LARVA IKAN TIGER CATFISH (Psedoplatystoma punctifer) DENGAN PENGKAYAAN MINYAK JAGUNG PADA Artemia sp. - Crisnawati Crisnawati; Achmad Noerkhaerin Putra, S.Pi., M.Si.; Mustahal Mustahal (Universitas Sriwijaya, 2023)
Corn oil is an essential fatty acid containing linoleic acid (n-6). This study aims to evaluate the different doses of corn oil in the Artemia sp. enrichment on the growth and survival of tiger catfish (Pseudoplatystoma punctifer) larvae. Tiger catfish larvae (initial weight of 0.004 g) were reared in an aquarium (30x20x20 cm) with a volume of 9 L for 15 days. Enrichment using corn oil was carried out six times a day with an enrichment duration of 4 hours, and every 4 hours continuously in each day for feeding. Three treatments with different doses: P0 (control), P1 (0.075 mL/L corn oil), P2 (0.225 mL/L corn oil) with three replications were used in the present study. The results showed that the enrichment of Artemia sp. have significant effect (p<0.05) on the growth of tiger catfish larvae than control (without enrichment). Artemia sp. enrichment with corn oil dosage of 0.225 mL/L produced the best results on final weight (0.11g), final length (24.30 mm), absolute weight growth (0.1 g), absolute length growth (20.33 mm), specific growth rate of weight (28.13 %.g/day) and specific growth rate of length (15.04 %.mm/day) of tiger catfish larvae compared to other treatments. Key words: Artemia sp., corn oil, enrichment, tiger catfish larvae